The relationship between the 1200 m shuttle test and 40 m sprint test performance and distances covered in English Premier League matches: A retrospective two season study - Kavanagh, Ronan; Matteotti, Matteo; Oliveira, Rafael; McDaid, Kevin; Alexander, Jill; Harper, Damian; Zmijewski, Piotr; Rhodes, David; Morgans, Ryland (Biology of Sport, 2025)
To identify a relationship between the 1200 m shuttle test and 40 m sprint test performance with distances covered at varying intensities in English Premier League (EPL) matches. A squad ( n = 21) of full-time professional 1 st team male football players (age 29.8±3.4 years; height 183.7±5.2 cm; weight 83.7±6.9 kg) participated in this study. League match data from the 2019–20 and 2020–21 seasons were recorded and analysed via an Optical Tracking System (OTS) (Second Spectrum®, Los Angeles, USA) to report physical match performance data. Average velocity during the 1200 m shuttle test (V1.2ST) was calculated, while Peak sprinting speed (PSS) was estimated using a 40 m maximal sprint. ASR1.2ST was established by subtracting V1.2ST from PSS. The relationship between V1.2ST, 30%ASR1.2ST and distances covered at varying intensities in EPL matches was assessed by a series of independent Linear Mixed Effects (LME) models. Although not statistically significant, for every unit increase in V1.2ST, there was an increase of 1032 m in distance covered, ( p = 0.07). A single unit increase in 30%ASR1.2ST is associated with a significant increase of 495 m in high-speed running distance (> 5.5 m·s −1 ) ( p = 0.02). While for each unit increase in 30%ASR1.2ST, sprint distance (> 7 m·s −1 ) covered significantly increased by 209 m ( p = 0.02). In conclusion, high levels of physical fitness such as V1.2ST and 30%ASR1.2ST derived from the 1200 m shuttle and 40 m sprint tests can improve match running performance in elite soccer. Knowledge of this information allows practitioners to tailor training load based on each players individual characteristics, potentially increasing performance.